A new genus and species of Apoloniinae (Acari: Trombiculidae) from Oman - Stekolnikov, Alexandr A.; Carranza, Salvador; Gomez-Diaz, Elena (Zootaxa, 2012)
A new chigger mite genus and species, Arabapolonia omanensis gen. nov. et sp. nov. is described from 4 gecko species,Hemidactylus lemurinus, H. homoeolepis (Gekkonidae), Ptyodactylus hasselquistii (Phyllodactylidae), and Pristurusrupestris (Sphaerodactylidae) collected in Oman. The new genus is characterized by the simple cheliceral blade, singlepalpal claw, palpal tarsus 6BS, non-reduced scutum without nasus bearing 2 AM, 2 AL and 2 PL setae, flagelliformsensilla branched in the distal half, 2 pairs of eyes, 7-segmented legs with onychotriches, the absence of some leg setae(subterminala, parasubterminala, pretarsalae I and II, microgenuala II, tibiala III, and coxala II), the absence of the sternal setae between leg coxae I (fSt = 0.2.4), and by the presence of tracheae.